2023
DOI: 10.1038/s43856-023-00252-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of transmitral and left atrial appendage flow rate from cardiac 4D-CT

Abstract: Background Cardiac time-resolved CT (4D-CT) acquisitions provide high quality anatomical images of the heart. However, some cardiac diseases require assessment of blood flow in the heart. Diastolic dysfunction, for instance, is diagnosed by measuring the flow through the mitral valve (MV), while in atrial fibrillation, the flow through the left atrial appendage (LAA) indicates the risk for thrombus formation. Accurate validated techniques to extract this information from 4D-CT have been lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The radiation exposure from CT can be substantially reduced with advanced dose modulation (13). Although CT does not provide inherent motion information, we previously showed that it allows for the extraction of the endocardial wall motion and that flow rates calculated from those data agree well with measurements from 4D flow MRI (14). Thus, time-resolved cardiac CT is an excellent tool to investigate the left atrial shape and function.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The radiation exposure from CT can be substantially reduced with advanced dose modulation (13). Although CT does not provide inherent motion information, we previously showed that it allows for the extraction of the endocardial wall motion and that flow rates calculated from those data agree well with measurements from 4D flow MRI (14). Thus, time-resolved cardiac CT is an excellent tool to investigate the left atrial shape and function.…”
Section: Introductionmentioning
confidence: 81%
“…For this, the endocardium of the LA and LV was segmented using ITK-SNAP version 3.8.0 ( www.itksnap.org ) ( 27 ) at the end diastolic time frame (0% RR) and the geometry was further processed with Ansys SpaceClaim version 2019 R3 (Ansys Inc, Canonsburg, PA 15317 USA). Then, the endocardial surface was deformed using a non-rigid iterative closed point algorithm to match threshold-based segmentations of the other 19 cardiac phases, as described previously ( 14 ). The approach yields similar flow rates as those obtained by 4D flow MRI ( 14 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, first reports show that closing the LAA may improve the LA flow dynamics measured by four-dimensional magnetic resonance imaging [83]. Recently, LAA four-dimensional flow analysis has also been applied to cardiac CT, with similar outcomes to magnetic resonance imaging [84].…”
Section: Flow Dynamicsmentioning
confidence: 99%
“…On the other hand, 4D flow MRI has a limited ability to capture rapid changes in blood flow dynamics and identify small or intricate flow features. An emerging alternative approach is the use of cardiac time-resolved CT (4D-CT), which offers better spatio-temporal resolution, but its validation is still in progress [22].…”
Section: Introductionmentioning
confidence: 99%